THE INFLUENCE OF HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE: THE MEDIATING ROLE OF COMPETENCY - Limrueangrong, Panitada; Thaweepaiboonwong , Jutamard (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2022)
This study was quantitative research which purposed to analyze the level of human resource development (HRD) practices, competency, and performance of employees working in the automotive parts industry in the Eastern Economic Corridor as well as to analyze the influence of HRD practices on employee performance by considering competency as a mediator variable. The data were collected by a questionnaire with a sample of 230 employees working in key units involved in the automotive parts manufacturing process. The statistics used for data analysis included percentage, mean, standard deviation, and structural equation modeling. The findings revealed that the level of HRD practices, competency and performance of employees were at a high level. The structural equation model for analyzing the influence of HRD practices on employee competency was consistent with the empirical data with values of 2/df = 2.747, GFI = 0.932, AGFI = 0.884, RMR = 0.015, RMSEA = 0.087. Employee performance was influenced both directly and indirectly by HRD practices, with competency serving as a partial mediator. The findings of the study confirm that the organization’s human resource development is critical to its success.